2020
DOI: 10.21203/rs.3.rs-45616/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey on Generative Adversarial Networks for imbalance problems in computer vision tasks

Abstract: Any computer vision application development starts off by acquiring images and data, then preprocessing and pattern recognition steps to perform a task. When the acquired images are highly imbalanced and not adequate, the desired task may not be achievable. Unfortunately, the occurrence of imbalance problems in acquired image datasets in certain complex real-world problems such as anomaly detection, emotion recognition, medical image analysis, fraud detection, metallic surface defect detection, disaster predic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 113 publications
(159 reference statements)
0
7
0
Order By: Relevance
“…In addition to heavy-equipment manufacturers and other companies using film inspection, most domestic companies have developed to CR and DR digital ray detection imaging technology for welding quality inspection [4][5][6]. In the defect assessment stage, due to the unevenness and diversity of the nature of defects such as form, location, direction, and size, making it difficult to find a set of common means and methods to automatically identify weld defects in the actual production process [7], the weld defects are usually assessed manually in the assessment process. In the process of manual evaluation of the film, first is to determine whether there are defects on the weld flaw detection image, then determine the type of defects, followed by the determination of defect data, and finally the quality level assessment according to the quality acceptance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to heavy-equipment manufacturers and other companies using film inspection, most domestic companies have developed to CR and DR digital ray detection imaging technology for welding quality inspection [4][5][6]. In the defect assessment stage, due to the unevenness and diversity of the nature of defects such as form, location, direction, and size, making it difficult to find a set of common means and methods to automatically identify weld defects in the actual production process [7], the weld defects are usually assessed manually in the assessment process. In the process of manual evaluation of the film, first is to determine whether there are defects on the weld flaw detection image, then determine the type of defects, followed by the determination of defect data, and finally the quality level assessment according to the quality acceptance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…92 While there exist other algorithms to synthesize data, such as the synthetic minority oversampling technique (SMOTE) 93 and adaptive synthetic sampling (ADASYN), 94 they are mostly suitable for tabular data, which restricts their application in high-dimensional complex image data. 95 DCGAN instead can generate synthetic images with high visual fidelity. When it was first introduced, Radford et al 92 identified an architecture that allows training the algorithm to generate higher-resolution images.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Generative Methods for Class Imbalance. Generative models can not only be used to generate images [17], but adversarial learning showed good potential in restoring balance in imbalanced datasets [18]. Generative models can generate samples that are difficult for the object detector to classify.…”
Section: Related Workmentioning
confidence: 99%